2013 35th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2013
DOI: 10.1109/embc.2013.6610948
|View full text |Cite
|
Sign up to set email alerts
|

Wireless patch sensor for remote monitoring of heart rate, respiration, activity, and falls

Abstract: Unobtrusive continuous monitoring of important vital signs and activity metrics has the potential to provide remote health monitoring, at-home screening, and rapid notification of critical events such as heart attacks, falls, or respiratory distress. This paper contains validation results of a wireless Bluetooth Low Energy (BLE) patch sensor consisting of two electrocardiography (ECG) electrodes, a microcontroller, a tri-axial accelerometer, and a BLE transceiver. The sensor measures heart rate, heart rate var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 3 publications
5
72
0
Order By: Relevance
“…It would be also difficult to ensure that the device is placed at the same position during the different experiments. In order to overcome this issue in future work, we envisage that devices that can be attached to the skin as patches will be commonly available to allow continuous and unobtrusive monitoring of gait [38]- [41]. In addition, we plan to investigate the use of the proposed technique on an ear-worn sensor.…”
Section: Resultsmentioning
confidence: 99%
“…It would be also difficult to ensure that the device is placed at the same position during the different experiments. In order to overcome this issue in future work, we envisage that devices that can be attached to the skin as patches will be commonly available to allow continuous and unobtrusive monitoring of gait [38]- [41]. In addition, we plan to investigate the use of the proposed technique on an ear-worn sensor.…”
Section: Resultsmentioning
confidence: 99%
“…The population was selected to be consistent with previous device performance validation studies [20] (K152139). Forty-four subjects were recruited with 30 participants enrolled: 77% male, 23% female, mean age of 35.9 ± 10.1 years (range 21–52), and a mean BMI of 28.1 ± 3.6 (range 20.1–34.1).…”
Section: Resultsmentioning
confidence: 99%
“…Comparator devices were selected to reproduce the identical validation previously published by the predicate device [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Several papers published by the manufacturer showed that the wireless patch records data in a robust and reliable way [19, 20]. The data recorded by the wireless patch were directly and continuously transferred to a connected iPod for the entire duration of the recording.…”
Section: Methodsmentioning
confidence: 99%